The subunit vaccine of Lumpy skin disease virus elicits significant humoral and cell-mediated immune responses in mice - Gu, Xiaoxiao; Deng, Xiaoyu; Wu, Aodi; Li, Honghuan; Liu, Ziwei; Wang, Wenxing; Ma, Zhongchen; Chen, Chuangfu (Frontiers in Veterinary Science, 2025)
Lumpy skin disease (LSD) is an emerging systemic and infectious disease affecting cattle. Currently, there is no specific treatment for this disease, and vaccination to boost immunity remains the most direct and effective approach for preventing LSD. In this study, we selected ORF073, ORF075, ORF090, and ORF110 proteins from the Lumpy skin disease virus (LSDV), which exhibit dominant antigenic properties, to construct, express, and identify recombinant prokaryotic expression vectors. The purified proteins were used to immunize mice. The immune efficacy of the subunit vaccines was preliminarily evaluated by monitoring antibody secretion and the expression of immune-related genes. The results showed that mice immunized with ORF075 and ORF090 subunit vaccines produced higher levels of antibody responses and induced a Th1/Th2-biased immune response. Splenocytes from immunized mice, when stimulated with vaccine antigens in vitro, exhibited the induction of higher levels of T-cell immune responses. These findings demonstrate that the LSDV ORF075 and ORF090 subunit vaccine developed in this study successfully induced robust humoral and cellular immune responses in mice, thereby providing a data foundation for subsequent experiments in the natural bovine host.